Changes in hotel activities in Ukraine and Poland due to the war: Migration aspect - Alla Okhrimenko; Margaryta Boiko; Myroslava Bosovska; Nadiia Vedmid; Mariia Kulyk (Problems and Perspectives in Management)
Internal displacement to safer regions and migration abroad became a new phenomenon in Ukraine due to Russian military aggression. Accordingly, hotels began to provide services to a new category of consumers – internally displaced persons (in Ukraine) and migrants (abroad). In 2022, Poland received the most migrants from Ukraine due to its geographical position and significant economic ties. This study aims to identify changes in hotel activities in Ukraine and Poland caused by internal and external migration. The results are based on Computer Assisted Web Interviewing (CAWI) conducted in April-July 2023, to which 300 hotels in Ukraine and Poland were invited. Answers were received from 93 Ukrainian and 94 Polish hotels. The majority (66% in Ukraine and 62% in Poland) have a star rating of 2-3*, with an average capacity of 45 rooms in Poland and 49 in Ukraine. According to hotel managers, the level of occupancy of hotels increased on average – in Ukraine by 6% and in Poland by 13%. The specific weight of migrants in hotels in Poland was 23% of all customers; in Ukraine, it was 12%. Hotels in both countries began to introduce new services, attract different sources of cost coverage (however, Polish hotels used wider opportunities), and attract migrants to employment (34% in Poland and 7.5% in Ukraine), contributing to additional occupancy rates and financial stability. Changes in hotel operations caused by migration processes as a result of the war reflect their adaptability and economic sustainability. Acknowledgment The paper shows the results of the study performed in 2021−2023 at State University of Trade and Economics at the request of the Ministry of Education and Science of Ukraine “Forecasting the impact of the tourism system on the country’s economy” (state registration number 0122U001559).The authors would like to express their gratitude to the Kirkland Research Program, the Leaders of Change Foundation, the Polish American Freedom Foundation, Polish Chamber of Commerce for Hotel Industry, and to those who helped to disseminate information about the survey, as well as to the Polish hotels and all those who expressed interest in the results.